Pemanfaatan Media Sosial Instagram BuddyKu Sebagai Sarana Informasi Terkini - Noventa, Christifera; Soraya, Iin; Muntazah, Arina (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
ABSTRACT Social media is a digital platform that enables its users to interact with each other by communicating and exchanging written, visual and audio information. This is because social media is a program that depends on the internet. The purpose of this research was to find out the utilization of Instagram BuddyKu social media as a means of up-to-date information. This study uses New Media theory where researchers use this theory as a measuring tool or support in this study because social media is present as this new media. This type of research uses descriptive qualitative methods with interviews and observations. The results of this study indicate that to seek information, BuddyKu makes several media portals a reference material for publishing on BuddyKu's Instagram social media. BuddyKu itself collects related information in all fields. BuddyKu also analyzes what news is trending on social media. BuddyKu processes content with an attractive design and simple headlines. BuddyKu focuses on the core of the discussion and there are illustrations so that the content is easier for the audience to understand.